High-frequency multimodal training with a focus on Tai Chi in people with Parkinson’s disease: a pilot study - Toloraia, Ketevan; Gschwandtner, Ute; Fuhr, Peter (Frontiers in Aging Neuroscience, 2024)
Background and Objectives: Cognitive decline is an important and common complication in patients with Parkinson’s disease (PD) since it significantly reduces the quality of life. A breakthrough in treating and preventing cognitive decline in PD remains to be achieved. This study aimed to evaluate the effectiveness of high-frequency and intensive multimodal training in improving motor and cognitive function. Methods: 28 patients diagnosed with idiopathic PD completed a comprehensive neuropsychological test battery and were neurologically examined. The patients of the intervention group (n=15) underwent 2 weekly sessions of Tai Chi therapy over 4 weeks and participated in an individually tailored training program consisting of two modules (smartphone-based speech training and cognitive training). A matched control group consisted of n=13 patients with PD who received computer-assisted cognitive training. The data were analyzed with repeated-measures ANOVA. Results: Four weeks of high-frequency training showed significant effects on verbal and figural episodic memory and visuospatial function in the intervention group. Compared to the control group, the cognitive performance of the intervention group improved significantly in visuospatial function and figural episodic memory. A significant improvement was also shown in the intervention group in the Tinetti Mobility Test and the Epworth Sleepiness Scale. The significant effects in the Tinetti mobility test remained after the six months follow-up. After the intervention, the patients reported high motivation and satisfaction with the multimodal training. Conclusion: In patients with PD, a multimodal training program not only improves gait and stability but may also contribute to improving cognition. Keywords: Parkinson’s disease, Tai Chi, cognititve decline, cognition, cognitive training, motor skills, neuropsychology, training, speech therapy, multimodal treatment